Pendidikan Lifelong Learning dalam Meningkatkan Kesiapan Tenaga Kerja di Indonesia Melalui Implementasi yang Efektif - Hidayat, Syarif; Saripulloh, Asep (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
In the era of Society 5.0, technological advances have changed the workforce's needs, demanding adaptive skills obtained through lifelong learning education. This study analyzes the implementation of lifelong learning policies in Indonesia, focusing on the Merdeka Belajar program and its impact on workforce readiness. The method used is a literature review, analyzing previous research, government reports, and policy documents to identify challenges and opportunities for lifelong learning implementation. The results show that although Merdeka Belajar provides flexibility in learning, there are significant barriers, such as digital access gaps and weak cross-sector collaboration. Best practice findings show that integrating technology in education and strengthening institutional partnerships can improve workforce adaptability. This research emphasizes the importance of more inclusive policies to align education in Indonesia with the evolving demands of the job market. Strategic recommendations focus on strengthening the digital learning ecosystem, promoting collaboration between government, industry, and educational institutions, and increasing public awareness of the importance of lifelong learning. With these steps, it is hoped that Merdeka Belajar’s policy can be more effective in improving workforce readiness in the digital era.